HUBUNGAN ANTARA HARAPAN SISWA (STUDENT EXPECTATION) TERHADAP GURU MATA PELAJARAN ILMU STATIKA DAN TEGANGAN DENGAN HASIL BELAJAR SISWA KELAS X PROGRAM KEAHLIAN TEKNIK BATU DAN BETON SMK NEGERI 5 PADANG TAHUN AJARAN 2014/2015. - 529-537 , Michael Sulaiman Halawa (Universitas Negeri Padang, 2015)
ABSTRACT The purpose of the research is knowing the relation between student expectations for teachers with student learning achievment in science subjects statics and voltage class X program expertise Stone and Concrete Engineering SMK N 5 Padang 2014/2015. This research is descriptive correlational. The number of samples in this study were 27 students, the selection of the sample using total sampling technique for a student population of just 27 students. Data were collected through questionnaires student expectations and learning outcomes data through documentation of the midterm results of class X program expertise Stone and Concrete Construction Engineering. Test requirements analysis using normality test, linearity and correlation test. The analytical method used is simple regression correlation analysis. The results of of research that there is a positive correlation between student expectation of student learning achievment, evidenced r hit price (0.889) greater than r tab (0.381). The coefficient of determination indicates that the contribution to the student learning achievment for 79%. It can be said that influence student expectation and students learning achievment are very high. Keywords: Students Expectation, Student Learning Achievment